Performance evaluation of a triangular-prism solar still using bagasse as a porous medium in the Malaysian climate - Md Yusop, Azdiana; Zakaria, Muhammad Hafizzullah; Muhammad Zaini, Jamal Zaim; Mohd Jahari @ Mohd Johari, Ahmad Nizam; Sulaiman, Noor Asyikin (Semarak Ilmu Publishing, 2024)
The Solar Still System is a technology that applies fundamental concepts of water evaporation and condensation, making it easier to turn unclean or salty water into potable water through solar heat energy. This study focuses on Triangular-Prism Solar Still (TPSS), which has a distinctive physical structure that uses large surface areas on both sides to promote the retention of high temperatures inside the Solar Still area. The difference in internal and external temperatures of the Solar Still will encourage the formation of clean water droplets and, with the inclination of each side wall, help collect clean water. This experiment uses a Galvanized Steel tray to act as Phase Change Material (PCM); 100ml was produced within 4 to 5 hours of the operation. Using sugarcane bagasse as porous material results in a 2% improvement in overall performance. With the help of Thermo Electric components, two units of Peltier improved the significant result by increasing the 5% TPSS humidity. This study also showed better performance when using clean water than dirty water.